Evaluating the co-digestion of bovine and goat excreta for biogas generation using a tubular biodigester in Valledupar, Cesar - Yassuana Britto López; Luis Quintero López; Jesús Manuel Epalza Contreras (Results in Engineering)
As the transition toward decentralized renewable energy becomes more urgent in rural Colombia, biogas production through anaerobic digestion presents a sustainable solution for waste valorization and energy access. This study evaluated the co-digestion of bovine and goat manure using a tubular biodigester under real operating conditions at La Esperanza farm in Valledupar, Cesar. Laboratory-scale biomethanization potential (BMP) assays identified a 75:25 goat-to-bovine ratio as optimal, reaching a methane (CH₄) yield of 0.1978 m3 CH₄ per kilogram of volatile solids (kgVS). Due to livestock availability, the full-scale implementation used a 75:25 bovine-to-goat mixture, resulting in 0.17 m3 CH₄/kgVS and 53.7 % CH₄ concentration, compared to 0.14 m3 CH₄/kgVS and 55.5 % CH₄ in mono-digestion. Physicochemical analysis showed that mono-digestion had greater organic matter removal—10.98 % volatile solids (VS) and 19.66 % total solids (TS)—compared to 4.72 % and 0.3 % in co-digestion. Both processes maintained stable pH (7.6–7.9), optimal volatile fatty acids/total alkalinity (VFA/TA) ratios, and no hydrogen sulfide (H₂S) generation, confirming system stability. The biodigester replaced up to 80 % of traditional fuels and reduced carbon dioxide (CO₂) emissions by 3–6 tons per year, with estimated annual savings of COP 650,000. No kinetic modeling was required, as BMP consistency between lab and field validated system predictability. This study demonstrates the feasibility of anaerobic digestion for small-scale energy production, emphasizing the importance of substrate availability, pretreatment of goat manure, and balanced feedstock design. Its results provide evidence-based guidance for implementing biodigesters in similar rural contexts to promote energy access, waste reduction, and environmental sustainability.